PENGARUH PUPUK KANDANG SAPI DAN PUPUK HAYATI MIKORIZA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) PADA TANAH PMK - Joni Kurniawan; Muhammad Nur (UIR Press, 2025)
This research aims to determine the main and interaction effects of cow manure and mycorrhizal biological fertilizer on the growth and production of shallot plants (Allium ascalonicum L.) on PMK soil. This research was carried out at the Experimental Farm of the Faculty of Agriculture, Islamic University of Riau, Jalan Kaharudin Nasution, KM 11 No. 113, Perhentian Marpoyan, Air Winter Village, Bukit Raya District, Pekanbaru City. The research was conducted over three months, from May to August 2023. This study used a factorial Completely Randomized Design (CRD) consisting of two factors. The first factor is the dose of cow manure (S), with four treatment levels: 0, 1.5, 3, and 4.5 kg/plot. The second factor is the dose of mycorrhizal biological fertilizer, with four treatment levels: 0, 200, 400, and 600 g/plot. The parameters observed were plant height, harvest age, number of tubers per cluster, wet weight per cluster, dry weight per cluster, and tuber weight loss. The observation data were analyzed statistically, and further Honest Significant Difference (BNJ) tests were conducted at the 5% level. The results indicate that the interaction effect of cow manure and mycorrhizal biological fertilizer has a significant impact on plant height, number of tubers per hill, wet weight per hill, dry weight per hill, and tuber weight loss. The interaction of cow manure and mycorrhizal biofertilizer has no significant effect on harvest age. The best treatment dose is 4.5 kg of cow manure per plot and 600 g of mycorrhizal biological fertilizer per plot. The main effect of cow manure was significant on all observation parameters, with the best treatment at a dose of 4.5 kg/plot. The main effect of mycorrhizal biological fertilizer was significant for all observation parameters, with the best treatment dose being 600 g/plot.